Bacterial Vaginosis and Behavioral Factors Associated With Incident Pelvic Inflammatory Disease in the Longitudinal Study of Vaginal Flora. (16th August 2021) - Turpin, Rodman; Tuddenham, Susan; He, Xin; Klebanoff, Mark A; Ghanem, Khalil G; Brotman, Rebecca M
Abstract: Background: Pelvic inflammatory disease (PID) leads to long-term reproductive consequences for cisgender women. Bacterial vaginosis (BV) and behavioral factors may play a role in PID pathogenesis. We assessed associations between BV, behavioral factors, and incident PID. Methods: We analyzed participants (N = 2956) enrolled in the National Institutes of Health Longitudinal Study of Vaginal Flora, a cohort of nonpregnant cisgender women followed quarterly for 12 months. PID was defined by at least 1 of the following: cervical motion tenderness, uterine tenderness, or adnexal tenderness (160 cases). We tested associations between BV (measured using Nugent and Amsel criteria) and PID at the subsequent visit. Sociodemographic factors, sexual behaviors, and Chlamydia trachomatis (CT), untreated at baseline and concurrent with BV, were covariates in Cox proportional hazards models. Adjusting for the few Neisseria gonorrhoeae and Trichomonas vaginalis cases did not alter results. Results: In multivariable modeling, Nugent-BV (adjusted hazard ratio [aHR], 1.53 [95% confidence interval CI, 1.05–2.21]), symptomatic Amsel-BV (aHR, 2.15 [95% CI, 1.23–3.75]), and vaginal douching (aHR, 1.47 [95% CI, 1.03–2.09]) were associated with incident PID. Conclusions: BV was associated with incident PID in a large prospective cohort, controlling for behavioral factors and sexually transmitted infections (STIs). Larger studies on how BV, STIs, behaviors, and host responses interactively affect PID risk are needed.